Pendidikan Islami Anak: Upaya Membangun Karakter Mulai Usia Dini - Zaenul Fitri, Agus (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2013)
The article is to raise parentsâ€™ awareness on the importance of early childhood education. It is not solely about sending their children to school to get knowledge.Â But the children are given space to grow and develop properly.Â If the children get a complete and comprehensive education, they will be an important human who becomes useful for society, nation, and religion.Â Education should make child healthy physically, mentalyl, emotionally.Â Education must include three aspects, namely cognitive, affective, and psychomotor which is not only to accompany a sensitivity and intelligence of student but also to know God almighty.